2023
DOI: 10.3389/feart.2022.1094415
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of flow field in a blast simulator combined-driven by explosive charge and compressed gas

Abstract: The flow field characteristics of blast simulators with the explosive-driven method and compression-driven method have been extensively investigated; however, limited effort has been made to the flow field in blast simulators combined-driven by explosive charge and compressed gas. In this paper, the finite volume method governed by the Navier–Stokes equation based on an explosive detonation and k-omega SST turbulence equation was used to analyze the flow field characteristics of blast simulators with three kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…In addition, the driving method also affects the waveform of the shock wave. Compared to the compression-driven method, the shock wave produced by the explosive-driven method is closer to the waveform of a free-field explosion [ 3 , 9 ]. Ren et al suggested that the multi-point detonation method reduced the structural strength requirements of the chamber compared to direct detonation in the chamber [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the driving method also affects the waveform of the shock wave. Compared to the compression-driven method, the shock wave produced by the explosive-driven method is closer to the waveform of a free-field explosion [ 3 , 9 ]. Ren et al suggested that the multi-point detonation method reduced the structural strength requirements of the chamber compared to direct detonation in the chamber [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The solution is suitable for high detonation, explosion safety, and general compressible flow conditions [ 26 ]. It can accurately simulate the explosion flow field in the shock tubes [ 3 ]. The numerical simulations use the Euler governing equation based on explosive detonation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation